A perovskite quantum dot composite material and its preparation method and application
By using alkaline earth metal-doped molecular sieve coating and passivation technology on perovskite quantum dots, the problems of instability and insufficient resistance of perovskite quantum dots are solved, and their water, oxygen, heat and blue light resistance are achieved. The photoluminescence efficiency and stability are enhanced.
Patent Information
- Application Number
- CN202310262950.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-17
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2043-03-17
AI Technical Summary
The prior art is difficult to effectively improve the water, oxygen, heat and blue light resistance of perovskite quantum dots, and its structure is unstable, affecting the photoluminescence efficiency and stability.
The perovskite quantum dots can be coated through alkaline earth metal-doped molecular sieve, which can not only protect the perovskite quantum dots through molecular sieve packaging, but also passivate the perovskite quantum dots using alkaline earth metal ions on the inner wall of the molecular sieve channel, reducing the Defect density and replace part of the silicon skeleton with alkaline earth metal to fix the perovskite quantum dot position to avoid lattice distortion.
The water, oxygen, heat and blue light resistance of perovskite quantum dots is significantly improved, and its photoluminescence efficiency and stability is enhanced. The preparation method is environmentally friendly and has low energy consumption, and has good commercial application prospects.
Smart Images

Figure CN116200186B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of luminescent materials, and in particular relates to a perovskite quantum dot composite material and a preparation method and application thereof. Background Art
[0002] Metal halide perovskite quantum dots (PQDs) have attracted much attention since their discovery due to their low cost, high photoluminescence efficiency, and adjustable emission wavelength. They are widely used in light-emitting diodes, detectors, and displays. The general chemical formula of PQDs is ABX3, where the A position is an organic small molecule (formamidinium ion FA + or methylamine ion MA + ) or monovalent metal cations (Cs + or Rb + ), B is a divalent cation (Pb 2+ or Sn 2+ ), X is a halide anion (Cl - Br - ,I - ). Compared with organic-inorganic PQDs, pure inorganic PQDs show higher thermal stability and more stable photoelectric properties. Although the stability of pure inorganic PQDs is higher than that of organic-inorganic PQDs, their formation energy is lower, resulting in their inherent structural instability, which makes their water resistance, oxygen resistance, heat resistance and blue light resistance still poor, and they cannot be truly industrialized.
[0003] At present, the methods for improving pure inorganic PQDs are usually ligand passivation, oxide encapsulation and metal ion doping. Among them, the most promising method is the molecular sieve encapsulation PQDs method in oxide encapsulation. The prior art literature (10.1038 / s41467-019-13881-0) points out that molecular sieve encapsulated PQDs can be prepared by high-temperature calcination of oxide mesoporous silica (MCM-41 molecular sieve) and PQDs precursor, which to a certain extent isolates water and oxygen from contact with PQDs and improves the water and oxygen stability of PQDs. However, this method still cannot improve the dry heat and blue light stability of PQDs. The patent (CN114316969A) points out that PQDs are encapsulated using molecular sieves, and alkaline earth metal salts are added during the calcination process. The alkaline earth metal ions can passivate the PQDs to a certain extent, reduce the defect density of the PQDs, and improve the heat resistance and blue light stability of the PQDs. However, the alkaline earth metal-passivated PQDs have no force interaction with the inner wall of the molecular sieve pores, and the PQDs cannot be further fixed. It is impossible to avoid the lattice distortion caused by the lattice vibration of the PQDs when they are exposed to heat and blue light, which destroys the photoluminescence efficiency and stability of the PQDs.
[0004] Therefore, how to effectively improve the water, oxygen, heat and blue light resistance of PQDs, while avoiding the lattice distortion caused by lattice vibration when PQDs are exposed to heat and blue light, which may damage the photoluminescence efficiency and stability of PQDs, is a technical problem that needs to be solved urgently. Summary of the invention
[0005] In view of the deficiencies of the prior art, the object of the present invention is to provide a composite material of perovskite quantum dots and a preparation method and application thereof. The present invention coats the perovskite quantum dots by alkaline earth metal-doped molecular sieves, which can not only encapsulate the perovskite quantum dots by the molecular sieves to protect the perovskite quantum dots from water and oxygen erosion, but also passivate the perovskite quantum dots by using the alkaline earth metal ions on the inner wall skeleton of the molecular sieve pores, reduce the defect density of the perovskite quantum dots, and improve the water, oxygen, heat and blue light resistance of the perovskite quantum dots. At the same time, the alkaline earth metal replaces part of the silicon skeleton, which can play a role in fixing the position of the perovskite quantum dots, avoiding the destruction of the photoluminescence efficiency and stability of the perovskite quantum dots by the lattice distortion caused by the lattice vibration when the perovskite quantum dots are subjected to heat and blue light, and further improves the heat resistance and blue light stability of the perovskite quantum dots.
[0006] To achieve this object, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a perovskite quantum dot composite material, wherein the perovskite quantum dot composite material comprises perovskite quantum dots and alkaline earth metal-doped molecular sieves coated on the surface of the quantum dots.
[0008] The present invention coats perovskite quantum dots by using alkaline earth metal-doped molecular sieves, which can not only encapsulate the perovskite quantum dots through the molecular sieves to protect the perovskite quantum dots from water and oxygen erosion, but also use the alkaline earth metal ions on the inner wall skeleton of the molecular sieve pores to passivate the perovskite quantum dots, reduce the defect density of the perovskite quantum dots, and improve the water, oxygen, heat and blue light resistance of the perovskite quantum dots. At the same time, the alkaline earth metal replaces part of the silicon skeleton to fix the position of the perovskite quantum dots, thereby avoiding the destruction of the photoluminescence efficiency and stability of the perovskite quantum dots caused by lattice distortion caused by lattice vibration when the perovskite quantum dots are subjected to heat and blue light, and further improving the heat resistance and blue light stability of the perovskite quantum dots.
[0009] Preferably, one end of the alkaline earth metal is connected to the inner wall of the molecular sieve channel, and the other end of the alkaline earth metal is connected to the quantum dot.
[0010] In the present invention, one end of the alkaline earth metal element that partially exchanges the molecular sieve framework element inside the molecular sieve pores is connected to the inner wall of the molecular sieve pores in the form of a covalent bond, which can stabilize the lattice of the perovskite quantum dots. The covalent bond at the other end is broken, and the perovskite quantum dots are passivated and protected in the form of ions. The perovskite quantum dot composite material with this structure has good stability and has good commercial application prospects.
[0011] Preferably, the molecular sieve comprises any one of SBA, MCM or ZSM, preferably MCM.
[0012] Preferably, the alkaline earth metal includes any one of Sr, Mg or Ca or a combination of at least two thereof, preferably Sr.
[0013] Preferably, based on the mass of the alkaline earth metal-doped molecular sieve, the doping amount of the alkaline earth metal is 0.5-2%, for example, it can be 0.5%, 0.6%, 0.8%, 1%, 1.2%, 1.4%, 1.6%, 1.8% or 2%.
[0014] In the present invention, if the doping amount of alkaline earth metal is too little, it is impossible to ensure that the alkaline earth metal effectively passivates the perovskite quantum dots; if the doping amount of alkaline earth metal is too much, it will greatly affect the pore collapse temperature of the molecular sieve.
[0015] Preferably, the perovskite quantum dots are inorganic perovskite quantum dots.
[0016] Preferably, the chemical formula of the inorganic perovskite quantum dot is ABX3, A is a monovalent metal cation, B is a divalent cation, and X is a halogen anion.
[0017] Preferably, the monovalent metal cation comprises Cs + .
[0018] Preferably, the divalent cations include Pb 2+ and / or Sn 2+ .
[0019] Preferably, the halogen anion includes any one of Cl-, Br- or I-, or a combination of at least two of them.
[0020] In a second aspect, the present invention provides a method for preparing the perovskite quantum dot composite material as described in the first aspect, the preparation method comprising the following steps:
[0021] (1) preparing alkaline earth metal-doped molecular sieves;
[0022] (2) Mixing the alkaline earth metal-doped molecular sieve and a perovskite quantum dot precursor, and calcining to obtain the perovskite quantum dot composite material.
[0023] The present invention prepares an alkaline earth metal-doped molecular sieve in advance, and then mixes and calcines a perovskite quantum dot precursor with an alkaline earth metal-doped molecular sieve. In the pre-prepared alkaline earth metal-doped molecular sieve channel, part of the alkaline earth metal element can exchange part of the molecular sieve framework element silicon to form a -Si-OM- (M is an alkaline earth metal, - is a covalent bond) structure, and the alkaline earth metal exists in the form of a covalent bond on the inner wall of the molecular sieve channel. During the calcination process, the covalent bond of one end of the alkaline earth metal element that partially exchanges the molecular sieve framework element silicon breaks, and the perovskite quantum dot is passivated and protected in the form of an ion, and the other end is connected to the silicon skeleton in the molecular sieve channel in the form of a covalent bond, stabilizing the lattice of the perovskite quantum dot, and finally preparing a perovskite quantum dot composite material. The perovskite quantum dot composite material improves the water resistance, oxygen, heat and blue light stability of the perovskite quantum dot through the combined effects of molecular sieve encapsulation, surface passivation and lattice doping. At the same time, the perovskite quantum dot composite material has good stability, simple purification method, low energy consumption, wide application range, and has good commercial application prospects.
[0024] In the preparation method provided by the present invention, the perovskite quantum dot composite material can be prepared without using polluted solvents, which is green and environmentally friendly.
[0025] Preferably, the specific steps of preparing the alkaline earth metal-doped molecular sieve in step (1) include:
[0026] The silicon source and the alkaline earth metal salt are mixed and reacted to obtain the alkaline earth metal-doped molecular sieve.
[0027] As a preferred technical solution of the present invention, the silicon source includes any one of silicon oxide, tetraethyl orthosilicate, methyl orthosilicate, isopropyl orthosilicate or butyl orthosilicate, or a combination of at least two thereof, preferably tetraethyl orthosilicate.
[0028] Preferably, the alkaline earth metal salt comprises a hydrohalide salt and / or an acetate salt of an alkaline earth metal. Exemplarily, the hydrohalide salt of an alkaline earth metal may be, for example, a chloride.
[0029] Preferably, the molar ratio of the alkaline earth metal salt to the silicon source is 1:(10-30), for example, it can be 1:10, 1:12, 1:14, 1:16, 1:18, 1:20, 1:22, 1:24, 1:26, 1:28 or 1:30, etc.
[0030] Preferably, a template is also added during the blending process of the silicon source and the alkaline earth metal salt.
[0031] Preferably, the template comprises hexadecyltrimethylammonium bromide and / or ethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer, and the ethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer is denoted as P123.
[0032] As a preferred technical solution of the present invention, the blending process is accompanied by stirring.
[0033] Preferably, the blending temperature is 60-100°C, for example, 60°C, 70°C, 80°C, 90°C or 100°C.
[0034] Preferably, the blending time is 4-12 h, for example, it can be 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, 11 h or 12 h.
[0035] Preferably, an acid-base regulator is also added during the blending process. The present invention does not limit the type of the acid-base regulator, and exemplary examples thereof include ethanolamine, sodium hydroxide, or hydrochloric acid.
[0036] Preferably, the blending method includes:
[0037] The template, alkaline earth metal salt and solvent are mixed, and an acid-base regulator is added to obtain a solution, and the solution is mixed with a silicon source.
[0038] Preferably, the pH value of the solution is 9-11 or 2-4, wherein the pH value selection range "9-11" can be, for example, 9, 10 or 11, etc., and the pH value selection range "2-4" can be, for example, 2, 3 or 4, etc.
[0039] As a preferred technical solution of the present invention, the mass ratio of the alkaline earth metal-doped molecular sieve and the perovskite quantum dot precursor in step (2) is (1-3):(1-3), wherein the selection range of the alkaline earth metal-doped molecular sieve "1-3" can be, for example, 1, 1.5, 2, 2.5 or 3, and the selection range of the perovskite quantum dot precursor "1-3" can be, for example, 1, 1.5, 2, 2.5 or 3, etc.
[0040] In the present invention, if the mass ratio of the alkaline earth metal doped molecular sieve to the perovskite quantum dot precursor is too small, that is, the amount of the alkaline earth metal doped molecular sieve is too small, some perovskite quantum dots cannot be completely wrapped and protected by the molecular sieve; if the mass ratio of the alkaline earth metal doped molecular sieve to the perovskite quantum dot precursor is too large, that is, the amount of the alkaline earth metal doped molecular sieve is too large, the photoluminescence efficiency of the perovskite quantum dots is affected to a certain extent.
[0041] Preferably, the mixing process in step (2) is accompanied by stirring.
[0042] Preferably, grinding is performed after the mixing in step (2).
[0043] As a preferred technical solution of the present invention, the heating rate of calcination in step (2) is 10-40°C / min, for example, it can be 10°C / min, 15°C / min, 20°C / min, 25°C / min, 30°C / min, 35°C / min or 40°C / min, and is preferably 15-25°C / min.
[0044] In the present invention, a calcination heating rate that is too fast or too slow will affect the product quality, because a too fast or too slow heating rate will make the furnace temperature difficult to control and the temperature in the furnace will not match the actual temperature.
[0045] Preferably, the calcination temperature in step (2) is 600-700°C, for example, 600°C, 620°C, 640°C, 660°C, 680°C or 700°C.
[0046] In the present invention, if the calcination temperature is too low, the molecular sieve will not collapse, resulting in the molecular sieve being unable to completely collapse and seal to protect the perovskite quantum dots from water and oxygen erosion; if the calcination temperature is too high, the molecular sieve skeleton will break, resulting in defects in the molecular sieve.
[0047] Preferably, the calcination time in step (2) is 10-60 min, for example, it can be 10 min, 15 min, 20 min, 25 min, 30 min, 35 min, 40 min, 45 min, 50 min, 55 min or 60 min.
[0048] Preferably, after the calcination in step (2) to obtain the perovskite quantum dot composite material, post-treatment is performed, and the specific steps of the post-treatment include:
[0049] The perovskite quantum dot composite material is cooled, washed and dried.
[0050] Preferably, the cooling time is 12-36 h, for example, it can be 12 h, 15 h, 18 h, 21 h, 24 h, 27 h, 30 h, 33 h or 36 h.
[0051] Preferably, the post-treatment step is repeated 2-4 times, for example, 2 times, 3 times or 4 times.
[0052] As a preferred technical solution, the preparation method comprises the following steps:
[0053] (I) mixing a template, an alkaline earth metal salt and a solvent, adding an acid-base regulator to obtain a solution with a pH value of ...9-11 or 2-4, mixing the solution and a silicon source at 60-100° C. and stirring for 4-12 hours to obtain an alkaline earth metal-doped molecular sieve, and washing the alkaline earth metal-doped molecular sieve with distilled water and ethanol for 2-4 times to obtain a purified alkaline earth metal-doped molecular sieve;
[0054] Wherein, the molar ratio of the alkaline earth metal salt to the silicon source is 1:(10-30);
[0055] (II) mixing and stirring the purified alkaline earth metal-doped molecular sieve and the perovskite quantum dot precursor, grinding, and then calcining at a temperature of 600-700° C. for 10-60 min to obtain a crude product of the perovskite quantum dot composite material;
[0056] Wherein, the mass ratio of the alkaline earth metal-doped molecular sieve to the perovskite quantum dot precursor is (1-3): (1-3);
[0057] (III) Cooling the crude product of the perovskite quantum dot composite material at room temperature for 12-36 hours, washing and drying to obtain a perovskite quantum dot composite material.
[0058] In the present invention, room temperature refers to 25±5°C, for example, it may be 20°C, 25°C or 30°C.
[0059] In a third aspect, the present invention provides a quantum dot device, wherein the quantum dot device comprises the perovskite quantum dot composite material as described in the first aspect.
[0060] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0061] Compared with the prior art, the present invention has the following beneficial effects:
[0062] (1) The present invention utilizes alkaline earth metal-doped molecular sieves to coat perovskite quantum dots, which can not only encapsulate the perovskite quantum dots through the molecular sieve to protect the perovskite quantum dots from water and oxygen erosion, but also utilize the alkaline earth metal ions on the inner wall skeleton of the molecular sieve pores to passivate the perovskite quantum dots, thereby reducing the defect density of the perovskite quantum dots and improving the water, oxygen, heat and blue light resistance of the perovskite quantum dots. At the same time, the alkaline earth metal replaces part of the silicon skeleton to fix the position of the perovskite quantum dots, thereby avoiding the lattice distortion caused by the lattice vibration of the perovskite quantum dots when exposed to heat and blue light, which damages the photoluminescence efficiency and stability of the perovskite quantum dots, thereby further improving the heat resistance and blue light stability of the perovskite quantum dots.
[0063] (2) The perovskite quantum dot composite material prepared by the present invention has good stability, simple purification method, low energy consumption, low pollution, wide application range, and good commercial application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0064] Figure 1 This is a schematic diagram of alkaline earth metal-doped molecular sieves in the process of preparing perovskite quantum dot composite materials in Example 1 of the present invention.
[0065] Figure 2 This is a diagram showing the mechanism of alkaline earth metal-doped molecular sieves forming a perovskite quantum dot composite material in Example 1 of the present invention.
[0066] Figure 3 This is a process flow chart for preparing a perovskite quantum dot composite material according to Example 1 of the present invention. DETAILED DESCRIPTION
[0067] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0068] In the embodiment of the present invention, room temperature refers to 25°C.
[0069] Example 1
[0070] The present embodiment provides a perovskite quantum dot composite material, which includes perovskite quantum dots (PQDs) and alkaline earth metal Sr-doped molecular sieve MCM coated on the surface of the quantum dots, denoted as Sr-MCM / CsPbBr3.
[0071] One end of the alkaline earth metal is connected to the inner wall of the molecular sieve channel in the form of a covalent bond, and the other end of the alkaline earth metal exists in the form of ions; the doping amount of the alkaline earth metal is 1.5%.
[0072] The present invention also provides a method for preparing a perovskite quantum dot composite material, such as Figure 3 As shown, the preparation method comprises the following steps:
[0073] (1) 5.48 mmol of hexadecyltrimethylammonium bromide and 2.5 mmol of strontium chloride were mixed in 700 mL of deionized water, and 2.5 mL of an aqueous solution of ethanolamine (concentration of 2 mmol / mL) was dropped to obtain a solution with a pH value of 11. The solution and 44.8 mmol of tetraethyl orthosilicate were mixed and stirred at 60° C. for 4 h to obtain an alkaline earth metal-doped molecular sieve. The alkaline earth metal-doped molecular sieve was washed three times with distilled water and ethanol to obtain a purified alkaline earth metal-doped molecular sieve, which was recorded as Sr-MCM.
[0074] Wherein, the molar ratio of strontium chloride to tetraethyl orthosilicate is 1:18;
[0075] (2) 0.6 g of the Sr-MCM and the perovskite quantum dot precursor (including 0.1272 g of CsBr and 0.22 g of PbBr2) were mixed and ground evenly, and placed in a ceramic boat, and then the ceramic boat was placed in a tube furnace, and the temperature was increased to 670° C. at a heating rate of 20° C. / min, and calcined at a constant temperature for 60 min to obtain a crude product of the perovskite quantum dot composite material;
[0076] Wherein, the mass ratio of the alkaline earth metal-doped molecular sieve to the perovskite quantum dot precursor is 0.6:0.3472;
[0077] (3) The crude product of the perovskite quantum dot composite material was cooled at room temperature for 24 hours, centrifugally washed with deionized water three times, and then dried in a vacuum drying oven at 60° C. to obtain a perovskite quantum dot composite material.
[0078] Figure 1 A schematic diagram of alkaline earth metal-doped molecular sieves in the process of preparing perovskite quantum dot composite materials in this embodiment is shown. As can be seen from the figure, alkaline earth metals replace part of the silicon skeleton to fix the position of the perovskite quantum dots, thereby avoiding the destruction of the photoluminescence efficiency and stability of the perovskite quantum dots by lattice distortion caused by lattice vibration when the perovskite quantum dots are subjected to heat and blue light, and further improving the heat resistance and blue light stability of the perovskite quantum dots.
[0079] Figure 2 The diagram shows the mechanism of the alkaline earth metal-doped molecular sieve forming a perovskite quantum dot composite material in this embodiment. As can be seen from the figure, the present invention can achieve the coating of the perovskite quantum dots by the alkaline earth metal-doped molecular sieve by mixing and calcining the alkaline earth metal-doped molecular sieve and the perovskite precursor. This process can not only encapsulate the perovskite quantum dots through the molecular sieve, but also partially exchange the alkaline earth metal elements of the molecular sieve skeleton elements inside the molecular sieve pores. One end is connected to the inner wall of the molecular sieve pores in the form of a covalent bond, thereby stabilizing the lattice of the perovskite quantum dots, and the covalent bond at the other end is broken, and the perovskite quantum dots are passivated and protected in the form of ions, thereby reducing the defect density of the perovskite quantum dots and improving the water-oxygen stability of the perovskite quantum dots.
[0080] Example 2
[0081] The difference between this embodiment and embodiment 1 is that the strontium chloride in step (1) is replaced by magnesium chloride, that is, the perovskite quantum dot composite material provided in this embodiment is Mg-MCM / CsPbBr3.
[0082] The rest of the preparation methods and parameters were the same as those in Example 1.
[0083] Example 3
[0084] The difference between this embodiment and embodiment 1 is that 0.22 g PbBr2 in step (1) is replaced by 0.27 g PbI2, that is, the perovskite quantum dot composite material provided in this embodiment is Sr-MCM / CsPbI3.
[0085] The rest of the preparation methods and parameters were the same as those in Example 1.
[0086] Example 4
[0087] The difference between this embodiment and embodiment 1 is that the strontium chloride in step (1) is replaced by magnesium chloride, and the 0.22 g PbBr2 in step (2) is replaced by 0.27 g PbI2, that is, the perovskite quantum dot composite material provided in this embodiment is Mg-MCM / CsPbI3.
[0088] The rest of the preparation methods and parameters were the same as those in Example 1.
[0089] Example 5
[0090] The present embodiment provides a perovskite quantum dot composite material, which includes perovskite quantum dots and alkaline earth metal Sr-doped molecular sieve SBA coated on the surface of the quantum dots, denoted as Sr-SBA / CsPbBr3.
[0091] One end of the alkaline earth metal is connected to the inner wall of the molecular sieve channel in the form of a covalent bond, and the other end of the alkaline earth metal exists in the form of ions; the doping amount of the alkaline earth metal is 1.5%.
[0092] The present invention also provides a method for preparing a perovskite quantum dot composite material, the preparation method comprising the following steps:
[0093] (1) 1.7 mmol of P123 and 1.25 mmol of strontium chloride were mixed in 50 mL of deionized water, and 2.5 mL of hydrochloric acid solution (concentration of 1 mmol / mL) was dropped to obtain a solution with a pH value of 2. The solution and 22.4 mmol of tetraethyl orthosilicate were added to a 100 mL hydrothermal kettle for mixing, and stirred at 100° C. for 12 h to obtain an alkaline earth metal-doped molecular sieve by reaction. The alkaline earth metal-doped molecular sieve was washed three times with distilled water and ethanol to obtain a purified alkaline earth metal-doped molecular sieve, which was recorded as Sr-SBA;
[0094] Wherein, the molar ratio of strontium chloride to tetraethyl orthosilicate is 1:18;
[0095] (2) 0.6 g of the Sr-SBA and the perovskite quantum dot precursor (including 0.1272 g of CsBr and 0.22 g of PbBr2) were mixed and ground evenly, and placed in a ceramic boat, and then the ceramic boat was placed in a tube furnace, and the temperature was increased to 670° C. at a heating rate of 20° C. / min, and calcined at a constant temperature for 60 min to obtain a crude product of the perovskite quantum dot composite material;
[0096] Wherein, the mass ratio of the alkaline earth metal-doped molecular sieve to the perovskite quantum dot precursor is 0.6:0.3472;
[0097] (3) The crude product of the perovskite quantum dot composite material was cooled at room temperature for 24 hours, centrifugally washed with deionized water three times, and then dried in a vacuum drying oven at 60° C. to obtain a perovskite quantum dot composite material.
[0098] Example 6
[0099] The present embodiment provides a perovskite quantum dot composite material, which includes perovskite quantum dots and alkaline earth metal Sr-doped molecular sieve ZSM coated on the surface of the quantum dots, denoted as Sr-ZSM / CsPbBr3.
[0100] One end of the alkaline earth metal is connected to the inner wall of the molecular sieve channel in the form of a covalent bond, and the other end of the alkaline earth metal exists in the form of ions; the doping amount of the alkaline earth metal is 0.5%.
[0101] The present invention also provides a method for preparing a perovskite quantum dot composite material, the preparation method comprising the following steps:
[0102] (1) 30 g of silica sol and 7 g of strontium chloride were added to 70 ml of deionized water to obtain modified sol A, 1.2 g of sodium hydroxide was dissolved in 47 ml of deionized water, 0.345 g of aluminum hydroxide was slowly added, and the mixture was stirred vigorously until the solution became suspended colloid B, and the suspended colloid B was slowly added to the modified sol A, and crystallized for 36 h to obtain Sr-ZSM;
[0103] (2) 0.6 g of the Sr-ZSM and the perovskite quantum dot precursor (including 0.1272 g of CsBr and 0.22 g of PbBr2) were mixed and ground evenly, and placed in a ceramic boat, and then the ceramic boat was placed in a tube furnace, and the temperature was increased to 600° C. at a heating rate of 10° C. / min, and calcined at a constant temperature for 40 min to obtain a crude product of the perovskite quantum dot composite material;
[0104] Wherein, the mass ratio of the alkaline earth metal-doped molecular sieve to the perovskite quantum dot precursor is 0.6:0.3472;
[0105] (3) The crude product of the perovskite quantum dot composite material was cooled at room temperature for 12 hours, centrifugally washed twice with deionized water, and then dried in a vacuum drying oven at 60° C. to obtain a perovskite quantum dot composite material.
[0106] Example 7
[0107] The present embodiment provides a perovskite quantum dot composite material, which includes a perovskite quantum dot core and an alkaline earth metal Ca-doped molecular sieve MCM coated on the surface of the core, denoted as Ca-MCM / CsPbBr3.
[0108] One end of the alkaline earth metal is connected to the inner wall of the molecular sieve channel in the form of a covalent bond, and the other end of the alkaline earth metal exists in the form of ions; the doping amount of the alkaline earth metal is 2%.
[0109] The present invention also provides a method for preparing a perovskite quantum dot composite material, the preparation method comprising the following steps:
[0110] (1) 5.48 mmol of hexadecyltrimethylammonium bromide and 1.49 mmol of calcium chloride were mixed in 700 mL of deionized water, and 2.5 mL of an aqueous solution of ethanolamine (concentration of 2 mmol / mL) was dropped to obtain a solution with a pH value of 11. The solution and 44.8 mmol of methyl orthosilicate were mixed and stirred at 60° C. for 4 h to obtain an alkaline earth metal-doped molecular sieve. The alkaline earth metal-doped molecular sieve was washed three times with distilled water and ethanol to obtain a purified alkaline earth metal-doped molecular sieve, which was recorded as Ca-MCM.
[0111] Wherein, the molar ratio of calcium chloride to tetraethyl orthosilicate is 1:30;
[0112] (2) 0.6 g of the Ca-MCM and the perovskite quantum dot precursor (including 0.1272 g of CsBr and 0.22 g of PbBr2) were mixed and ground evenly, and placed in a ceramic boat, and then the ceramic boat was placed in a tube furnace, and the temperature was increased to 700° C. at a heating rate of 40° C. / min, and calcined at a constant temperature for 10 min to obtain a crude product of the perovskite quantum dot composite material;
[0113] Wherein, the mass ratio of the alkaline earth metal-doped molecular sieve to the perovskite quantum dot precursor is 0.6:0.3472;
[0114] (3) The crude product of the perovskite quantum dot composite material was cooled at room temperature for 36 hours, centrifugally washed with deionized water four times, and then dried in a vacuum drying oven at 60° C. to obtain a perovskite quantum dot composite material.
[0115] Example 8
[0116] The difference between this embodiment and embodiment 1 is that the doping amount of the alkaline earth metal in the perovskite quantum dot composite material is 0.3%.
[0117] The rest of the preparation methods and parameters were the same as those in Example 1.
[0118] Example 9
[0119] The difference between this embodiment and embodiment 1 is that the doping amount of the alkaline earth metal in the perovskite quantum dot composite material is 2.2%.
[0120] The rest of the preparation methods and parameters were the same as those in Example 1.
[0121] Example 10
[0122] The difference between this embodiment and embodiment 1 is that in step (2), the mass ratio of the alkaline earth metal-doped molecular sieve to the perovskite quantum dot precursor is 0.06:0.3472.
[0123] The rest of the preparation methods and parameters were the same as those in Example 1.
[0124] Embodiment 11
[0125] The difference between this embodiment and embodiment 1 is that in step (2), the mass ratio of the alkaline earth metal-doped molecular sieve to the perovskite quantum dot precursor is 1.2:0.3472.
[0126] The rest of the preparation methods and parameters were the same as those in Example 1.
[0127] Example 12
[0128] The difference between this embodiment and embodiment 1 is that the calcination temperature in step (2) is 550°C.
[0129] The rest of the preparation methods and parameters were the same as those in Example 1.
[0130] Embodiment 13
[0131] The difference between this embodiment and embodiment 1 is that the calcination temperature in step (2) is 850°C.
[0132] The rest of the preparation methods and parameters were the same as those in Example 1.
[0133] Comparative Example 1
[0134] The difference between this comparative example and Example 1 is that no strontium chloride is added in step (1), that is, the obtained molecular sieve is pure MCM.
[0135] The rest of the preparation methods and parameters were the same as those in Example 1.
[0136] Comparative Example 2
[0137] The difference between this comparative example and Example 1 is that in step (1), no strontium chloride is added to obtain pure MCM; in step (2), MCM, a perovskite quantum dot precursor and 0.22 g of strontium chloride are mixed to obtain a perovskite quantum dot composite material, recorded as MCM / Sr-CsPbBr3.
[0138] The rest of the preparation methods and parameters were the same as those in Example 1.
[0139] Performance Testing
[0140] The perovskite quantum dot composite materials prepared in Examples 1-13 and Comparative Examples 1-2 were tested for photoluminescence efficiency under dry heat aging, photoluminescence efficiency under blue light aging, and water and oxygen stability.
[0141] The test results are shown in Table 1.
[0142] Table 1
[0143]
[0144]
[0145] analyze:
[0146] It can be seen from the above table that the perovskite quantum dot composite material provided by the present invention has excellent heat resistance and blue light stability, indicating that the coating of the perovskite quantum dots by alkaline earth metal-doped molecular sieves can not only physically encapsulate the perovskite quantum dots to isolate water and oxygen, but also fix the lattice of the perovskite quantum dots through the action of chemical bonds, passivate the surface defects of the perovskite quantum dots, and further improve the blue light and dry heat stability.
[0147] It can be seen from the data results of Example 1 and Examples 2-7 that the preparation method provided by the present invention has universal applicability and can be applied to perovskite quantum dots synthesized by different types of molecular sieves doped with different alkaline earth metals.
[0148] By comparing the data results of Example 1 with those of Examples 8-9, it can be seen that if the doping amount of the alkaline earth metal is too little, it is impossible to ensure that the alkaline earth metal effectively passivates the perovskite quantum dots; if the doping amount of the alkaline earth metal is too much, it will greatly affect the pore collapse temperature of the molecular sieve, resulting in a decrease in stability.
[0149] By comparing the data results of Example 1 with those of Examples 10-11, it can be seen that if the mass ratio of the alkaline earth metal-doped molecular sieve and the perovskite quantum dot precursor is too small, that is, the amount of the alkaline earth metal-doped molecular sieve is too small, some of the perovskite quantum dots cannot be completely wrapped and protected by the molecular sieve, resulting in a decrease in heat resistance and blue light stability; if the mass ratio of the alkaline earth metal-doped molecular sieve and the perovskite quantum dot precursor is too large, that is, the amount of the alkaline earth metal-doped molecular sieve is too much, the photoluminescence efficiency of the perovskite quantum dots is affected to a certain extent.
[0150] By comparing the data results of Example 1 with those of Examples 12-13, it can be seen that if the calcination temperature is too low, the molecular sieve will not collapse, resulting in the molecular sieve being unable to completely collapse and seal to protect the perovskite quantum dots from water and oxygen erosion, affecting the water and oxygen stability of the perovskite quantum dots; if the calcination temperature is too high, the molecular sieve skeleton will break, resulting in defects in the molecular sieve, thereby affecting the heat resistance and blue light stability of the perovskite quantum dots.
[0151] By comparing the data results of Example 1 with those of Comparative Examples 1-2, it can be seen that alkaline earth metals can passivate perovskite quantum dots and improve their resistance to dry heat and blue light. Pre-doping alkaline earth metals into the molecular sieve framework can further fix and stabilize the lattice of perovskite quantum dots and improve their resistance to dry heat and blue light.
[0152] The applicant declares that the present invention illustrates the process of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A perovskite quantum dot composite material, characterized in that: The perovskite quantum dot composite material comprises perovskite quantum dots and an alkaline earth metal-doped molecular sieve coated on the surface of the quantum dots; wherein the alkaline earth metal-doped molecular sieve comprises: mixing a silicon source and an alkaline earth metal salt to react to obtain the alkaline earth metal-doped molecular sieve; The molecular sieve includes any one of SBA, MCM or ZSM; The alkaline earth metal includes any one of Sr, Mg or Ca or a combination of at least two thereof; One end of the alkaline earth metal is connected to the inner wall of the molecular sieve channel in the form of a covalent bond, and the other end of the alkaline earth metal exists in the form of an ion and is connected to the quantum dot.
2. The perovskite quantum dot composite material according to claim 1, characterized in that The molecular sieve is MCM.
3. The perovskite quantum dot composite material according to claim 1, characterized in that: The alkaline earth metal is Sr.
4. The perovskite quantum dot composite material according to claim 1, characterized in that: Based on the mass of the alkaline earth metal-doped molecular sieve, the doping amount of the alkaline earth metal is 0.5-2%.
5. The perovskite quantum dot composite material according to claim 1, characterized in that: The perovskite quantum dots are inorganic perovskite quantum dots.
6. A method for preparing a perovskite quantum dot composite material according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: (1) Preparing an alkaline earth metal-doped molecular sieve, the specific steps comprising: mixing a silicon source and an alkaline earth metal salt, and reacting to obtain the alkaline earth metal-doped molecular sieve; (2) Mixing the alkaline earth metal-doped molecular sieve and a perovskite quantum dot precursor, and calcining to obtain the perovskite quantum dot composite material.
7. The preparation method according to claim 6, characterized in that: The silicon source includes any one of silicon oxide, ethyl orthosilicate, methyl orthosilicate, isopropyl orthosilicate or butyl orthosilicate, or a combination of at least two of them.
8. The preparation method according to claim 6, characterized in that: The alkaline earth metal salt includes chloride and / or acetate of alkaline earth metal.
9. The preparation method according to claim 7, characterized in that: The silicon source is tetraethyl orthosilicate.
10. The preparation method according to claim 6, characterized in that: The molar ratio of the alkaline earth metal salt to the silicon source is 1:(10-30).
11. The preparation method according to claim 6, characterized in that: A template is also added during the blending process of the silicon source and the alkaline earth metal salt.
12. The preparation method according to claim 11, characterized in that: The template agent includes hexadecyltrimethylammonium bromide and / or ethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer.
13. The preparation method according to claim 6, characterized in that: The blending process is accompanied by stirring.
14. The preparation method according to claim 6, characterized in that: The blending temperature is 60-100°C.
15. The preparation method according to claim 6, characterized in that: The blending time is 4-12 hours.
16. The preparation method according to claim 6, characterized in that: Acid-base regulator is also added during the blending process.
17. The preparation method according to claim 6, characterized in that: The blending method includes: The template, alkaline earth metal salt and solvent are mixed, and an acid-base regulator is added to obtain a solution, and the solution is mixed with a silicon source.
18. The preparation method according to claim 17, characterized in that: The pH value of the solution is 9-11 or 2-4.
19. The preparation method according to claim 6, characterized in that: In step (2), the mass ratio of the alkaline earth metal-doped molecular sieve to the perovskite quantum dot precursor is (1-3):(1-3).
20. The preparation method according to claim 6, characterized in that: The mixing process in step (2) is accompanied by stirring.
21. The preparation method according to claim 6, characterized in that: After the mixing in step (2), grinding is performed.
22. The preparation method according to claim 6, characterized in that: The heating rate of the calcination in step (2) is 10-40°C / min.
23. The preparation method according to claim 6, characterized in that: The heating rate of the calcination in step (2) is 15-25°C / min.
24. The preparation method according to claim 6, characterized in that: The calcination temperature in step (2) is 600-700°C.
25. The preparation method according to claim 6, characterized in that: The calcination time in step (2) is 10-60 minutes.
26. The preparation method according to claim 6, characterized in that: After the perovskite quantum dot composite material is obtained by calcination in step (2), post-treatment is performed. The specific steps of the post-treatment include: The perovskite quantum dot composite material is cooled, washed and dried.
27. The preparation method according to claim 26, characterized in that: The cooling time is 12-36h.
28. A quantum dot device, characterized in that: The quantum dot device comprises the perovskite quantum dot composite material as described in any one of claims 1 to 5.
Citation Information
Patent Citations
Perovskite quantum dot, preparation method thereof and quantum dot device
CN114316969A
Blue, yellow and orange light calcium titanium mining quantum dot and molecular sieve composite luminescent material and preparing method and application thereof
CN106701070A
Preparation method of composite perovskite luminous material
CN109337683A